The Recorder Education Journal no. 5 - Lasocki, David (Arta, 1999)
Baroque Ornamentation I. In this issue: - The Philosophy of Baroque Ornamentation Skills. - Developing Baroque Ornamentation Skills. - The Accidental Ornamentor. - Ornaments in the Duets of Pierre Danican Philidor. - The Doubles in Jacques Hotteterre's Airs et brunettes.II. In this issue: - A Curriculum for Teaching Ornamentation. - The Ornamentation of Arcangelo Corelli's Violin Sonatas, Op. 5. - J.S. Bach's Violin Ornaments Arranged by Interval. - J.S. Bach's Ornamentation of Slow Movements by Marcello and Vivaldi. - Learning to Ornament Handel's Sonatas Through the Composer's Ears.
Keywords: Hotteterre, Jacques-Martin -- 1673-1763; Corelli, Arcangelo -- 1653-1713; Bach, Johann Sebastian -- 1685-1750; Marcello, Benedetto -- 1686-1739; Vivaldi, Antonio -- 1678-1741; Handel, George Frideric -- 1685-1759; 17th Century (1601-1700); 18th Century (1701-1800); Historically informed performance; Recorder; Ornamentation